Determinants Of Financial Distress In The Coal Industry With Corporate Governance As A Moderation - Anissa Indaranti Adhiningrum; Dwi Prastowo Darminto; Rafrini Amyulianthy (Economics and Business Journal (ECBIS), 2026)
This study examines the effects of financial performance, sales growth, and corporate governance on financial distress, as well as the moderating role of corporate governance in the coal industry in Indonesia. The population consists of 33 coal companies listed on the Indonesia Stock Exchange (IDX), with 21 companies selected using purposive sampling. The study uses secondary data with 105 observations from 2019–2023. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that financial performance and corporate governance significantly affect financial distress, while sales growth has no significant effect. In addition, corporate governance does not moderate the relationship between financial performance and financial distress, nor between sales growth and financial distress. These findings highlight the importance of financial management and governance mechanisms in mitigating financial distress risk in the coal industry.